METHODOLOGICAL GUIDELINES OF PSYCHOLOGICAL PREVENTION AND PSYCHOLOGICAL CORRECTION OF EMOTIONAL BURNOUT MANIFESTATIONS OF TEACHERS - Demyanchuk, Roman V.; Sorokin, Viktor M.; Bloch, Maria E.; Schukin, Anton V.; Demyanov, Iyrii G. (International Journal of Psychosocial Rehabilitation, 2020)
The research problem considered in the article is the study of the foundations and guidelines for the organization and content of psychological prevention of emotional burnout of teachers. Using the method of diagnostics of the emotional burnout, V. V. Boyko examined 502 teachers, including 264 people working in special (correctional) educational institutions (the average age is 41,06 years old), 238 people are in General education (the average age is 39.95). The author analyzes the symptoms of emotional burnout and the manifestations of its formation phases (according to the model of V. V. Boyko). Significant differences in the studied groups of teachers have been established basing on the signs of experiencing psychotraumatic circumstances, feeling of beingb"caged" and inadequate selective emotional response, as well as on the frequency parameter of signs of the resistance phase. Based on the dominance of similarity of signs in the manifestations of emotional burnout of the teachers of the studied groups, the author has concluded that it is possible to develop a unified model of psychological prevention of emotional burnout of teachers, regardless of the type of educational institution. A number of guidelines for the organization and content of psychological work with teachers, based on the creation of conditions for their psychological support and technology of psychological support, based on the process approach, are proposed.